ANALISIS KESULITAN GURU SEKOLAH DASAR DALAM MELAKSANAKAN PEMBELAJARAN BERORIENTASI NUMERASI - Hardhita, Rizki Septa; Untari, Sri; Suciptaningsih, Oktaviani Adhi; Surayanah, Surayanah (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This study aims to analyse the challenges faced by elementary school teachers in implementing numeracy-oriented learning. Through qualitative research methods, including observation, interviews and document analysis, this study explores the experiences of teachers at SD Laboratorium UM Blitar. The research findings show the existence of internal and external barriers. Internal barriers include teachers‘ limited understanding of numeracy, students’ varied abilities, and inadequate pedagogical skills. External challenges include limited resources, curriculum limitations and heavy workloads. To improve numeracy education, this study recommends comprehensive teacher training, curriculum reform and increased resource allocation.